Doss Porphyria (δ-Aminolevulinic Acid Dehydratase Porphyria) Presenting with Acute Onset Flaccid Paralysis - Singh, Sandip Kumar; Gauchan, Eva; Koirala, Deepak Prasad; Rao, KS (Journal of Nepal Paediatric Society, 2016)
δ–Aminolevulinic acid dehydratase porphyria is an autosomal recessive disorder of heme synthesis resulting from deficiency of δ-aminolevulinic acid dehydratase (ALAD). Patients present with fatal neurovisceral manifestations and motor neuropathy. Here we report a patient with rapidly progressive flaccid tetraplegia with respiratory and bulbar paralysis. The importance of early diagnosis, prompt treatment and screening of relatives is stressed. J Nepal Paediatr Soc 2015;35(3):280-282